An electrochromic cathode material and an electrochromic solution and a preparation method thereof

The method of forming polymer-based block polymers through in-situ polymerization has solved the problem of irreversible discoloration and uneven discoloration after long-term power-up, and the material is guaranteed to have a stable dispersion and discoloration effect under the action of an electric field.

CN117430784BActive Publication Date: 2025-03-11NINGBO YINGLING PHOTOELECTRIC TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311325804.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-03-11
Estimated Expiration
2043-10-12

AI Technical Summary

Technical Problem

The existing electrochromic cathode materials are prone to cause discoloration and irreversible after long-term power-up, and the fading process is uneven.

Method used

By polymerizing the cathode color-changing material in situ, polymer-based block polymer is formed, which reduces the migration speed of the material under the action of an electric field and avoids over-migration and polarization.

Benefits of technology

It is realized that during the long-term power-up process, the cathode material can still be dispersed in the solution well, ensuring the color distortion effect and performance stability of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117430784B_ABST
    Figure CN117430784B_ABST
Patent Text Reader

Abstract

The invention discloses an electrochromic cathode material, which is a polymer-based block polymer generated by the reaction of component ①, component ②, and component ③, wherein component ① is a bipyridyl salt material modified by side chain grafting. A method for preparing an electrochromic solution is to dissolve 0.5-2.5 parts of component ①, 0.02-0.2 parts of component ②, 2-10 parts of component ③ together with an electrochromic solution anode material in 100 parts of a solvent, and after uniform dispersion, the filtrate is poured into an empty box of the device, and after sealing, the empty box of the device is placed in an oven and treated at a temperature of 60-120°C for 3 to 10 hours to obtain an electrochromic cathode material. Its advantages are: by means of in-situ polymerization, it is made into a polymer gel state, which reduces the speed of migration to the negative electrode, and in the long-term power-on process, it is still well dispersed in the solution without excessively gathering to one side, thereby ensuring the color change effect of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochromic material preparation, in particular to an electrochromic cathode material and an electrochromic solution and a preparation method thereof. Background Art

[0002] Electrochromism refers to the phenomenon that the optical properties of a material (reflectivity, transmittance, absorptivity, etc.) undergo stable and reversible color changes under the action of an external electric field, which is manifested in the reversible changes of color and transparency. Materials with electrochromic properties are called electrochromic materials, and devices made of electrochromic materials are called electrochromic devices.

[0003] During the electrochromic process, the electrochromic solution contains cathode color-changing materials and anode color-changing materials. These two materials are colorless in the solution under normal circumstances. When direct current is applied to the device, the cathode material migrates to the negative electrode to gain electrons, and the anode material migrates to the positive electrode to lose electrons. At this time, the color of the material or the absorption peak changes greatly, making the solution appear colored, which is the so-called electrochromism.

[0004] Among the electrochromic materials in the prior art, small molecule cathode color-changing materials have a small relative molecular weight. During the color-changing process, the small molecule cathode color-changing materials are easy to migrate to both sides of the electrode under the action of the electric field, so that when the power-on time is long, the fading process is prone to unevenness. What's worse, when the power-on time is too long, the small molecule cathode color-changing materials migrate excessively, resulting in a long fading time or even no fading.

[0005] For example, bipyridine materials, as a cathode electrochromic material, have a good coloring effect. However, during the color change process, if the power is applied for a long time, the ions of the cathode color change material are easy to migrate to the positive electrode because of the electrons gained, and the anodic color change material is easy to migrate to the negative electrode because of the loss of electrons, resulting in polarization at both ends, causing the two to aggregate on both sides of the positive and negative electrodes. During the fading process, the excessively aggregated ions at both ends of the positive and negative electrodes cannot be quickly restored to their original state, and may even cause irreversible color change, seriously affecting the performance of the product. Therefore, the existing electrochromic cathode materials need to be further improved. Summary of the invention

[0006] The purpose of the present invention is to make up for the above-mentioned deficiencies and disclose to the public an electrochromic cathode material and an electrochromic solution and a preparation method thereof which can avoid the irreversible color change caused by excessive migration of the color-changing material.

[0007] The technical solution of the present invention is achieved in this way:

[0008] An electrochromic cathode material, wherein the electrochromic cathode material is a polymer-based block polymer generated by reacting component ①, component ②, and component ③.

[0009] Among them, component ① is a side-chain grafted modified bipyridyl salt material, and its structural formula is:

[0010]

[0011] Its +2 valence is colorless, and its +1 valence is color developing, wherein: R1, R2 are electron withdrawing groups or electron donating groups, R3, R4 are alkylene groups, and X is BF4 or PF6;

[0012] The structural formula of component ② is:

[0013] The structural formula of component ③ is:

[0014] As an improvement, the R1 and R2 are electron-withdrawing groups, and R1 and R2 are respectively one of tertiary amine cation, nitro, trihaloalkyl, cyano, sulfonic acid, formyl, and acyl.

[0015] As an improvement, R1 and R2 are electron-donating groups, and R1 and R2 are respectively one of dialkylamino, alkylamino, amino, hydroxyl, alkoxy, alkyl, and phenyl.

[0016] As an improvement, in the R3 and R4, the C atoms of the alkylene are 2-20, and R3 and R4 are respectively one of a straight-chain alkylene primary alkane, a secondary alkane, a tertiary alkane or a cycloalkylene.

[0017] As an improvement, the component ③ is polyhydroxyethyl methacrylate, and the degree of polymerization n is between 10-1000.

[0018] An electrochromic solution comprises component ①, component ②, component ③ and an anode material required for the electrochromic solution.

[0019] A method for preparing an electrochromic solution comprises the following steps: dissolving 0.5-2.5 parts of component ①, 0.02-0.2 parts of component ②, 2-10 parts of component ③ and an anode material required for the electrochromic solution in 100 parts of a solvent, and after uniform dispersion, pouring the obtained filtrate into an empty box of a device, sealing the empty box of the device, placing it in an oven and treating it at a temperature of 60-120° C. for 3 to 10 hours to obtain an electrochromic solution based on a polymer cathode color-changing material, wherein the above parts are parts by mass.

[0020] As an improvement, the preparation method of the component ① comprises the following steps:

[0021] Step a, in a three-necked flask, 60mmol 2-propylhydroxy-4-bromopyridine, 88mmol 2-propylhydroxy-4-boric acid pyridine, 1.12mmol Pd2(DBA)3, 2.56mmol P(Cy)3, and 160ml dioxane are added in sequence, and 152mmol potassium carbonate dissolved in 160ml deoxygenated water is added to the three-necked flask using a syringe under nitrogen protection; after being evenly dispersed, it is placed in a 60°C oil bath, and then slowly heated to 100°C and refluxed, stirred for 18 hours, and then cooled to room temperature; the reactants are poured into a separating funnel for stratification, the organic phase is collected and filtered, the filtrate is subjected to rotary evaporation to volatilize and remove the dioxane, the residual solid is dissolved in 300ml ethyl acetate, and then treated with activated carbon and anhydrous sodium sulfate, heated to reflux for 10min under stirring, filtered, and the filtrate is subjected to rotary evaporation to volatilize the solvent to obtain the target product 2,2-propylhydroxy-4,4-bipyridine;

[0022] Step b, 38.6 g of bromoheptane and 97.6 g of 2,2-propylhydroxy-4,4-bipyridine and 1.0 L of acetonitrile were charged into a 2L three-necked round-bottom flask equipped with a reflux condenser, a mechanical stirrer and a heating jacket, and the reaction slurry was heated to reflux while stirring under positive nitrogen pressure; after 144 hours, the reaction was cooled to room temperature, and a crude product was obtained by vacuum filtration, which was then washed with ethanol and then with acetone, and the obtained product was heated in a vacuum drying oven at 60° C. for 4 h to obtain a purified dibromide salt;

[0023] Step c, add the dibromide salt together with 200 ml of acetone, 500 ml of deionized water and 500 ml of 50% ammonium hexafluorophosphate aqueous solution into a 2L round-bottom flask, heat the obtained compound to reflux to dissolve, and then cool to room temperature, during which the target product 1,1-diheptyl-2,2-propylhydroxy-4,4-bipyridyl dihexafluorophosphate forms a precipitate, collect the product by filtration, wash with deionized water, and then recrystallize with methanol, and place the crystallized product in a vacuum drying oven at 60°C for 8 hours to obtain component ①.

[0024] As an improvement, the preparation method of component ③ comprises the following steps: 100 grams of hydroxyethyl methacrylate, 120 grams of anhydrous ethanol, and 0.5 grams of azobisisobutyronitrile are placed in a 500 ml three-necked flask and dispersed evenly, nitrogen is passed through the flask for 30 minutes to remove the oxygen in the flask, and then placed in a 60°C oil bath for heating and reaction for 12 hours. At this time, a colloidal transparent substance appears in the bottle, which is poured into a container and solidified after cooling; it is dispersed into fine particles with a blender, and then placed in a vacuum drying oven at 100°C for drying for 5 hours to obtain component ③.

[0025] The advantages of the present invention compared with the prior art are:

[0026] The present invention converts the cathode color-changing material into a polymer gel state by in-situ polymerization, so that it can obtain electrons. At the same time, due to the large molecular volume, the migration speed to the negative electrode is reduced, so that it can still be well dispersed in the solution during long-term power-on without excessively gathering to one side, thereby ensuring the color-changing effect of the device. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The light transmittance spectrum of the color-changing cathode material device of the present invention after different voltages are applied to the two electrodes. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0029] An electrochromic cathode material, wherein the electrochromic cathode material is a polymer-based block polymer generated by reacting component ①, component ②, and component ③.

[0030] Among them, component ① is a side-chain grafted modified bipyridyl salt material, and its structural formula is:

[0031]

[0032] Its +2 valence is a colorless state, and its +1 valence is a colored state. It is worth noting that although its 0 valence is colored, its reversibility is poor, that is, once it reaches a valence of 0, the device is prone to irreversible damage.

[0033] Wherein: R1, R2 are electron withdrawing groups or electron donating groups, R3, R4 are alkylene groups, and X is BF4 or PF6;

[0034] The structural formula of component ② is:

[0035] The structural formula of component ③ is:

[0036] The R1 and R2 are electron-withdrawing groups, and R1 and R2 are respectively one of tertiary amine cation (-N+R3), nitro (-NO2), trihaloalkyl (-RX3, X=F, Cl), cyano (-CN), sulfonic acid (-SO3H), formyl (-CHO), and acyl (-COR).

[0037] The R1 and R2 are electron-donating groups, and R1 and R2 are respectively one of dialkylamino (-NR2), alkylamino (-NHR), amino (-NH2), hydroxyl (-OH), alkoxy (-OR), alkyl (-R), and phenyl (-Ph).

[0038] In the R3 and R4, the number of carbon atoms of the alkylene group is 2-20, and R3 and R4 are respectively one of a straight-chain alkylene group selected from primary alkane, secondary alkane, tertiary alkane or cycloalkylene group.

[0039] The component ② is isophorone diisocyanate.

[0040] The component ③ is polyhydroxyethyl methacrylate, and the degree of polymerization n is between 10-1000.

[0041] An electrochromic solution comprises component ①, component ②, component ③ and an anode material required for the electrochromic solution.

[0042] A method for preparing an electrochromic solution comprises the following steps: dissolving 0.5-2.5 parts of component ①, 0.02-0.2 parts of component ②, 2-10 parts of component ③ and an anode material required for the electrochromic solution in 100 parts of a solvent, and after uniform dispersion, pouring the obtained filtrate into an empty box of a device, sealing the empty box of the device, placing it in an oven and treating it at a temperature of 60-120° C. for 3 to 10 hours to obtain an electrochromic solution based on a polymer cathode color-changing material, wherein the above parts are parts by mass.

[0043] The above solvent is one of γ-butyrolactone, propylene carbonate, ethylene carbonate, and N-methylpyrrolidone, or a mixture of two thereof.

[0044] The preparation method of component ① comprises the following steps:

[0045] Step a, in a three-necked flask, 60mmol 2-propylhydroxy-4-bromopyridine, 88mmol 2-propylhydroxy-4-boric acid pyridine, 1.12mmol Pd2(DBA)3, 2.56mmol P(Cy)3, and 160ml dioxane are added in sequence, and 152mmol potassium carbonate dissolved in 160ml deoxygenated water is added to the three-necked flask using a syringe under nitrogen protection; after being evenly dispersed, it is placed in a 60°C oil bath, and then slowly heated to 100°C and refluxed, stirred for 18 hours, and then cooled to room temperature; the reactants are poured into a separating funnel for stratification, the organic phase is collected and filtered, the filtrate is subjected to rotary evaporation to volatilize and remove the dioxane, the residual solid is dissolved in 300ml ethyl acetate, and then treated with activated carbon and anhydrous sodium sulfate, heated to reflux for 10min under stirring, filtered, and the filtrate is subjected to rotary evaporation to volatilize the solvent to obtain the target product 2,2-propylhydroxy-4,4-bipyridine;

[0046] Step b, 38.6 g of bromoheptane and 97.6 g of 2,2-propylhydroxy-4,4-bipyridine and 1.0 L of acetonitrile were charged into a 2L three-necked round-bottom flask equipped with a reflux condenser, a mechanical stirrer and a heating jacket, and the reaction slurry was heated to reflux while stirring under positive nitrogen pressure; after 144 hours, the reaction was cooled to room temperature, and a crude product was obtained by vacuum filtration, which was then washed with ethanol and then with acetone, and the obtained product was heated in a vacuum drying oven at 60° C. for 4 h to obtain a purified dibromide salt;

[0047] Step c, add the dibromide salt together with 200 ml of acetone, 500 ml of deionized water and 500 ml of 50% ammonium hexafluorophosphate aqueous solution into a 2L round-bottom flask, heat the obtained compound to reflux to dissolve, and then cool to room temperature, during which the target product 1,1-diheptyl-2,2-propylhydroxy-4,4-bipyridyl dihexafluorophosphate forms a precipitate, collect the product by filtration, wash with deionized water, and then recrystallize with methanol, and place the crystallized product in a vacuum drying oven at 60°C for 8 hours to obtain component ①.

[0048] The preparation method of component ③ comprises the following steps: 100 grams of hydroxyethyl methacrylate, 120 grams of anhydrous ethanol, and 0.5 grams of azobisisobutyronitrile are placed in a 500 ml three-necked flask and dispersed evenly, nitrogen is passed through the flask for 30 minutes to remove oxygen in the flask, and then the flask is placed in a 60°C oil bath for heating and reaction for 12 hours. At this time, a colloidal transparent substance appears in the flask, which is poured into a container and becomes solid after cooling; the flask is dispersed into fine particles using a blender, and then placed in a vacuum drying oven at 100°C for drying for 5 hours to obtain component ③.

[0049] A voltage of 0.8-1.5V was applied to the two electrodes of the electrochromic cathode material device of the present invention, and its transmittance under different voltages was tested. The test results are as follows: Figure 1 As shown, Figure 1 The horizontal axis is the wavelength and the vertical axis is the transmittance. The electrochromic material of the present invention is divided into two states: a fading state and a colored state. Figure 1 From top to bottom in the figure are line 1, line 2, line 3 and line 4, line 1 is the spectrum curve of the faded state, line 2 is the spectrum curve of the colored state under the voltage of 0.8 V, line 3 is the spectrum curve of the colored state under the voltage of 1.0 V, and line 4 is the spectrum curve of the colored state under the voltage of 1.2 V. The electrochromic material of the present invention has different coloring effects under different voltages, and the greater the voltage, the deeper the coloring and the lower the transmittance.

[0050] The electrochromic cathode material device of the present invention that has been subjected to polymerization treatment is compared with the electrochromic cathode material device that has not been subjected to polymerization treatment. In the experiment, the device is subjected to voltage treatment for 1h / 2h / 4h / 8h / 16h at different voltages, and the fading process of the device is compared. The electrochromic cathode material device that has not been subjected to polymerization treatment has obvious yellow-blue separation phenomenon in fading after 1h of power-on; while the electrochromic cathode material of the present invention has very good fading uniformity after 2h of power-on after polymerization reaction, and no obvious yellow-blue separation phenomenon occurs. When the power is on for more than 4h, there is slight yellow-blue separation when fading begins, but it can be quickly restored to a normal fading state within 10s.

[0051] The electrochromic cathode material of the present invention grafts a small molecule cathode material onto a polymer molecular chain, so that it maintains the color-changing performance, and forms a whole with the polymer macromolecule, so that it is difficult to migrate in one direction, thereby reducing the polarization phenomenon and reducing the problem of uneven fading after long-term power-on. Through in-situ polymerization, it is turned into a polymer gel state, so that it obtains electrons. At the same time, due to the large molecular volume, the speed of its migration to the negative electrode is reduced, so that it can still be well dispersed in the solution during long-term power-on without excessively gathering to one side, ensuring the color-changing effect of the device. The electrochromic cathode material of the present invention can be widely used in the field of electrochromism, such as automotive anti-glare rearview mirrors, smart dimming glasses, smart dimming cameras, electrochromic smart windows, automotive glass and other fields.

[0052] In the electrochromic solution, the content of component ① will directly affect the transmittance of the device. The more component ① is present, the lower the transmittance is. On the contrary, the less component ① is present, the higher the transmittance is.

[0053] The following table is a spectrum data analysis table of transmittance at different component ① contents:

[0054]

[0055]

[0056]

[0057]

[0058] Among them, the first column corresponds to different wavelengths, and the second to ninth columns correspond to the transmittances under different contents of component ① (group 1 to group 8, from group 1 to group 8, the content of component ① gradually increases), and 8 groups of transmittance data are obtained.

[0059] Comparative experiment: Device preparation: Use two pieces of 30*30mm square conductive glass, with a single side offset of 2mm, and stick the conductive surfaces together. Use glue along the edge to stick them together, and leave a single opening hole for filling liquid. Use 100-micron microspheres to separate the middle to form a cavity, and make it ready for use.

[0060] (1) 0.95 parts of component ①, 0.12 parts of component ②, 3.5 parts of component ③ and the anode material required for the electrochromic solution were dissolved in 100 parts of γ-butyrolactone, and after being evenly dispersed, the obtained filtrate was poured into an empty box of the device, and after sealing, the empty box of the device was placed in an oven at 90° C. for 6 hours to prepare an electrochromic solution containing a polymer cathode material. The measured data correspond to the third group of data in the above table.

[0061] (2) 1.85 parts of component ①, 0.06 parts of component ②, 5.13 parts of component ③ and the anode material required for the electrochromic solution were dissolved in 100 parts of propylene carbonate, and after being evenly dispersed, the obtained filtrate was poured into an empty box of the device, and after sealing, the empty box of the device was placed in an oven at 100° C. for 4 hours to prepare an electrochromic solution containing a polymer cathode material. The measured data correspond to the seventh group of data in the above table.

[0062] As an extension, the thickness of the middle spacer box in the device preparation can be set arbitrarily between 50-300 microns. The contents of component ①, component ②, and component ③ can be adjusted appropriately, wherein component ①: 0.5-2.5 parts, component ②: 0.02-0.2 parts, component ③: 2-10 parts, the solvent can be any one of γ-butyrolactone, propylene carbonate, ethylene carbonate, N-methylpyrrolidone or any combination of two in any proportion, the oven treatment temperature can be between 60-120°C, and the time can be set arbitrarily between 3-10 hours. According to the device performance spectrum curve composed of the self-set composition, the data in groups 1 to 8 in the spectrum data can be selected, according to the principle that the higher the concentration of component ①, the darker the coloring, the lower the transmittance, and the closer to the data of group 8.

[0063] The best embodiment of the present invention has been described, and various changes or modifications may be made by those skilled in the art without departing from the scope of the present invention.

Claims

1. An electrochromic cathode material, characterized in that: The electrochromic cathode material is a polymer-based block polymer generated by the reaction of component ①, component ②, and component ③. Among them, component ① is a side-chain grafted modified bipyridyl salt material, and its structural formula is: Its +2 valence is colorless, and its +1 valence is color developing, wherein: R1, R2 are electron withdrawing groups or electron donating groups, R3, R4 are alkylene groups, and X is BF4 or PF6; The structural formula of component ② is: The structural formula of component ③ is:

2. The electrochromic cathode material according to claim 1, characterized in that: The R1 and R2 are electron-withdrawing groups, and R1 and R2 are respectively one of tertiary amine cation, nitro, trihaloalkyl, cyano, sulfonic acid, formyl and acyl.

3. The electrochromic cathode material according to claim 1, characterized in that: The R1 and R2 are electron-donating groups, and R1 and R2 are respectively one of dialkylamino, alkylamino, amino, hydroxyl, alkoxy, alkyl, and phenyl.

4. The electrochromic cathode material according to claim 1, characterized in that: In the R3 and R4, the number of carbon atoms of the alkylene group is 2-20, and R3 and R4 are respectively one of a straight-chain alkylene group selected from primary alkane, secondary alkane, tertiary alkane or cycloalkylene group.

5. The electrochromic cathode material according to claim 1, characterized in that: The component ③ is polyhydroxyethyl methacrylate, and the degree of polymerization n is between 10-1000.

6. An electrochromic solution, characterized in that: The electrochromic solution comprises component ①, component ②, component ③ as described in claim 1 and an anode material required for the electrochromic solution.

7. The method for preparing an electrochromic solution according to claim 6, characterized in that: Dissolve 0.5-2.5 parts of component ①, 0.02-0.2 parts of component ②, 2-10 parts of component ③ together with the anode material required for the electrochromic solution in 100 parts of solvent, and after uniform dispersion, pour the obtained filtrate into an empty box of the device. After sealing, put the empty box of the device into an oven and treat it at 60-120°C for 3 to 10 hours to obtain an electrochromic solution based on a polymer cathode color-changing material. The above-mentioned parts are all parts by mass.

8. The method for preparing an electrochromic solution according to claim 7, characterized in that: The preparation method of component ① comprises the following steps: Step a, in a three-necked flask, 60mmol 2-propylhydroxy-4-bromopyridine, 88mmol 2-propylhydroxy-4-boric acid pyridine, 1.12mmol Pd2(DBA)3, 2.56mmol P(Cy)3, and 160ml dioxane are added in sequence, and 152mmol potassium carbonate dissolved in 160ml deoxygenated water is added to the three-necked flask using a syringe under nitrogen protection; after being evenly dispersed, it is placed in a 60°C oil bath, and then slowly heated to 100°C and refluxed, stirred for 18 hours, and then cooled to room temperature; the reactants are poured into a separating funnel for stratification, the organic phase is collected and filtered, the filtrate is subjected to rotary evaporation to volatilize and remove the dioxane, the residual solid is dissolved in 300ml ethyl acetate, and then treated with activated carbon and anhydrous sodium sulfate, heated to reflux for 10min under stirring, filtered, and the filtrate is subjected to rotary evaporation to volatilize the solvent to obtain the target product 2,2-propylhydroxy-4,4-bipyridine; Step b, 38.6 g of bromoheptane and 97.6 g of 2,2-propylhydroxy-4,4-bipyridine and 1.0 L of acetonitrile were charged into a 2L three-necked round-bottom flask equipped with a reflux condenser, a mechanical stirrer and a heating jacket, and the reaction slurry was heated to reflux while stirring under positive nitrogen pressure; after 144 hours, the reaction was cooled to room temperature, and a crude product was obtained by vacuum filtration, which was then washed with ethanol and then with acetone, and the obtained product was heated in a vacuum drying oven at 60° C. for 4 h to obtain a purified dibromide salt; Step c, add the dibromide salt together with 200 ml of acetone, 500 ml of deionized water and 500 ml of 50% ammonium hexafluorophosphate aqueous solution into a 2L round-bottom flask, heat the obtained compound to reflux to dissolve, and then cool to room temperature, during which the target product 1,1-diheptyl-2,2-propylhydroxy-4,4-bipyridyl dihexafluorophosphate forms a precipitate, collect the product by filtration, wash with deionized water, and then recrystallize with methanol, and place the crystallized product in a vacuum drying oven at 60°C for 8 hours to obtain component ①.

9. The method for preparing an electrochromic solution according to claim 7, characterized in that: The preparation method of component ③ comprises the following steps: 100 grams of hydroxyethyl methacrylate, 120 grams of anhydrous ethanol, and 0.5 grams of azobisisobutyronitrile are placed in a 500 ml three-necked flask and dispersed evenly, nitrogen is passed through the flask for 30 minutes to remove oxygen in the flask, and then the flask is placed in a 60°C oil bath for heating and reaction for 12 hours. At this time, a colloidal transparent substance appears in the flask, which is poured into a container and becomes solid after cooling; the flask is dispersed into fine particles using a blender, and then placed in a vacuum drying oven at 100°C for drying for 5 hours to obtain component ③.

Citation Information

Patent Citations

  • Electrochromic compounds with improved color stability in their radical states

    CN107406389A

  • A composition for forming solution-type electrochromic layer, and electrochromic layer and electrochromic device prepared therefrom

    CN112631033A